2014
DOI: 10.3390/molecules191221239
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive A3B Porphyrin Nanomaterial for CO2 Detection

Abstract: Abstract:The present report deals with the tailoring, preparation and characterization of novel nanomaterials sensitive to CO2 for use in detection of this gas during space habitation missions. A new nanostructured material based on mixed substituted asymmetrical A3B porphyrin: 5-(4-pyridyl)-10,15,20-tris(3,4-dimethoxyphenyl)-porphyrin (PyTDMeOPP) was synthesized and characterized by 1 H-NMR, FT-IR, UV-vis, fluorescence, MS, HPLC and AFM. Introducing one pyridyl substituent in the 5-meso-position of porphyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
(33 reference statements)
1
13
0
1
Order By: Relevance
“…7). AFM analysis showed that the behavior of the cobalt porphyrin is in accordance with our previous studies [17,26] regarding the morphology and aggregation architectures of porphyrin derivatives from different solvents. The nanosized particles of Co-3OHPP are evenly oriented, have the shape of uniform triangular lamels and are displayed at different depths (Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…7). AFM analysis showed that the behavior of the cobalt porphyrin is in accordance with our previous studies [17,26] regarding the morphology and aggregation architectures of porphyrin derivatives from different solvents. The nanosized particles of Co-3OHPP are evenly oriented, have the shape of uniform triangular lamels and are displayed at different depths (Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Specifically for compound 4c, we observe the formation of J-aggregates that showed a red-shifted absorption band at 432 nm. 37 This phenomenon indicated that the molecules of compound 4c have side-by-side interactions in an ethanolic solution. Usually, porphyrins derived from cardanol have good solubility in solvents with low polarity such as chloroform (µ = 1.04), dichloromethane (µ = 1.60) and THF (µ = 1.75), but they are insoluble in polar solvents like acetone (µ = 2.88).…”
Section: Electronic Absorption and Luminescence Spectramentioning
confidence: 97%
“…Dalam penelitian ini protoporfirin IX muncul pada serapan kuat di 408 nm dan 2 serapan lemah di 556 nm dan 598 nm. Jika dibandingkan dengan penelitian Fagadar-cosma et al (2014) didapat serapan kuat dari senyawa turunan porfirin yakni 5-(4-pyridyl)-10,15,20-tris(3,4-dimethoxyphenyl) porfirin pada 423 nm dan terdapat 4 serapan lemah di 516 nm; 553 nm; 593 nm; dan 650 nm dalam pelarut metanol dan HCl 0,1N. Hal ini dikarenakan perbedaan subtituen dari tiap senyawa turunan porfirin yang ada sangat berpengaruh dan pelarut yang digunakan.…”
Section: Hasil Dan Pembahasan Ekstraksi Protoporfirin IXunclassified